From Reactive to Reflective: Pappaseng-AI's Innovation in Crisis Management Digital-Age Students' Metacognition Based on Local Culture - Apandi Astrid; Ramadhani Lutfiah; Pakanan Anastasia Nola; Alifah Sahlaa; Aswar Aswar (ILIN Education Indonesia, 2026)
The widespread use of generative artificial intelligence (AI) among students has triggered the emergence of an instant-answer culture, which is gradually weakening students' metacognitive abilities. Most students in Indonesia now utilize generative AI in their learning, but few applications are specifically designed to stimulate metacognitive reflection. This situation is further exacerbated by the low integration of local wisdom as a pedagogical approach, particularly in South Sulawesi. This article aims to examine the metacognitive crisis in the use of generative AI, to outline the epistemological values of Pappaseng as the basis for a reflective system, and to develop a conceptual framework for Pappaseng-AI as an alternative pedagogical solution based on local culture. The research was conducted using a qualitative approach using the Literature Study and Review (LSR) method. The study results indicate that the values of Pappaseng, amaccang, agettengeng, and sipakainge have strong epistemological alignment with components of modern metacognition. Based on this synthesis, Pappaseng-AI was formulated as a five-stage pedagogical framework that reconstructs students' interaction patterns with AI, from simply receiving answers to a process of co-constructing understanding through reflective questioning. The application of this framework is projected to increase metacognitive awareness, strengthen academic self-efficacy, and shape students' epistemic identities that are rooted in local wisdom and remain adaptive to global digital developments.